2011
DOI: 10.1111/j.1471-4159.2011.07352.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo electrochemical evidence for simultaneous 5‐HT and histamine release in the rat substantia nigra pars reticulata following medial forebrain bundle stimulation

Abstract: Exploring the mechanisms of serotonin (5-hydoxytryptophan (5-HT)) in the brain requires an in vivo method that combines fast temporal resolution with chemical selectivity. Fast-scan cyclic voltammetry (FSCV) is a technique with sufficient temporal and chemical resolution for probing dynamic 5-HT neurotransmission events; however, traditionally it has not been possible to probe in vivo 5-HT mechanisms. Recently, we optimized FSCV for measuring 5-HT release and uptake in vivo in the substantia nigra pars reticul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 66 publications
6
97
0
Order By: Relevance
“…Distinct storage and releasable pools for both 5-HT and dopamine have been described (31,32), but the large difference in their relative size had not previously been appreciated. Moreover, we previously noted that evoked release of 5-HT in the SNr is much lower in vivo compared with its electrically evoked release from SNr slice preparations (14). This suggests that in vivo 5-HT release is subject to tighter control mechanisms than both 5-HT in slices and dopamine in vivo.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Distinct storage and releasable pools for both 5-HT and dopamine have been described (31,32), but the large difference in their relative size had not previously been appreciated. Moreover, we previously noted that evoked release of 5-HT in the SNr is much lower in vivo compared with its electrically evoked release from SNr slice preparations (14). This suggests that in vivo 5-HT release is subject to tighter control mechanisms than both 5-HT in slices and dopamine in vivo.…”
Section: Resultsmentioning
confidence: 96%
“…Varying the dorsoventral location of the stimulating electrode revealed that 5-HT release can be evoked over greater region than dopamine, suggesting that serotonergic fibers have a broader topographic distribution. However, this is not sufficient to explain the 300-fold greater release of dopamine because even direct stimulation of serotonergic cell bodies in the dorsal raphe evokes comparably low 5-HT release (14).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As dopamine levels in the NAcc are considered important for reward-processing and motivation, and since FSL rats exhibit an abnormal serotonergic system [35,82], it was proposed that impairment in the serotonindopamine interactions could be related to the behavioral abnormalities of FSL rats [33,81]. As the rewarding effect of MFB stimulation has repeatedly been associated with activation of the serotonergic system [63,[91][92][93] this leads us to speculate that the effect of MFB-DBS in combination with haloperidol might be due to serotonergic-dopaminergic interaction. This could also explain why this effect is only seen in control but not in FSL rats.…”
Section: Vmpfc-and Mfb-dbs Differentially Affect Reward-seeking Behavmentioning
confidence: 99%
“…14,21,22 In addition to fouling problems, the pattern of brain 5-HT innervation has also contributed a challenge to in vivo FSCV measurement. While FSCV allows identification of individual monoamines, it does not allow the separate quantification of 5-HT and DA when they are simultaneously present at the electrode.…”
Section: ■ Challenges To Exploring Fscv Detectionmentioning
confidence: 99%